E-learning in Iraqi universities: a review - Mahmod, Mohamed Ali; Md Ali, Asma; Ahlan, Abdul Rahman; Shah, Asadullah; Abu Seman, Muhamad Sadry (Institute of Electrical and Electronics Engineers Inc., 2018)
Electronic Learning (e-learning) is considered as an innovative approach to education delivery via electronic forms of information. e-learning is an online education or distance education, which means that it can deliver education to everyone around the world online through the electronic means such as the internet from different distant countries. The success of E-learning process in universities needs to some factors that should be fit with the revolution of technology and enhance the learner's knowledge. Universities in developing countries such as Iraq, in order to be fit with the rapid growth of technology, it needs to analyze the current capabilities, analyzing previous studies, evaluating it and developing solutions fit with the updated technology in which these countries could save the time and reduce the cost and offer modern alternative means, tools, and methods of e-learning in its universities This paper reviews e-learning studies and status in Iraqi universities, identifying gaps and proposed some alternative solutions for that in order to enhance the e-learning process in Iraqi universities.